Manajemen Strategi Kerjasama Antar Daerah dalam Meningkatkan Desentralisasi Ekonomi Pasar - Deby Eprilianto; Dian Febri Artanti (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2023)
Changes in economic conditions during the covid-19 pandemic, triggered a decline in the level of the economy in Indonesia. The impact of these events resulted in a weakening of public purchasing power at large. The government is optimistic about implementing the National Economic Recovery (PEN) program, both nationally and through regional authorities specifically in East Java Province. The East Java Provincial Government took the initiative to create a trade mission program, involving cooperation between partner provinces. Through the implementation of the trade mission program, the government is collaborating with several agencies, especially the Department of Trade and Industry, regional apparatus organizations, and business actors. This study aims to identify and analyze the strategic management of the Department of Industry and Trade in developing small, medium and large industries to increase the market economy between the provincies of East Java and North Sulawesi. The method used in this research is qualitative research. Data collection used through observation, interviews and documentation. The results of the study show that the trade mission program between East Java and North Sulawesi from three aspects of strategic management, which shows the good implementation of programs such as environmental monitoring, strategy formulation and strategy implementation which play a role in reducing the market economy inflation rate. Even so it is necessary to make improvements to other aspects in order to have a sustainable impact on the implementation of the dagang mission program being carried out.